COMPOSTAGEM DE RESÍDUOS ORGÂNICOS EM INSTITUIÇÕES CARENTES - Júnior, Elói Meinen; Sippert, Luciane; De Freitas, Evandro; Da Silva, Danni Maisa; Lanzanova, Mastrangello Enivar; Kerkfof, Maristela Raquel (Salão do Conhecimento, 2018)
Projeto de extensão realizado no curso de agronomia da UERGS